2012
DOI: 10.1097/mbp.0b013e3283503760
|View full text |Cite
|
Sign up to set email alerts
|

Automated office versus home measurement of blood pressure in the assessment of morning hypertension

Abstract: The AOBP technique could replace mHBP monitoring in the assessment of morning BP, as it provides comparable data in relation to the awake ambulatory BP. Given the simplicity of this method, it could be more readily applied in a larger number of individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 0 publications
3
14
0
Order By: Relevance
“…Mean AOBP was 129/79 mm Hg compared with a mean daytime ABPM of 128/79 mm Hg, whereas oscillometric result was 134/84 mm Hg and the auscultatory result was 132/83 mm Hg, suggesting that AOBP is a more accurate technique than conventional office measurements in the evaluation of an individual's true BP status. Our findings concur with previous results showing similar values for mean AOBP and daytime ABPM, with both values being significantly lower than conventional office readings; this also suggests that white coat hypertension was significantly more prevalent when routine OBP readings were analyzed 6, 8, 16, 17. Staessen et al reviewed 30 studies in which conventional office readings were compared with daytime ABPM in untreated patients with borderline or definite hypertension; their findings showed that mean OBP was 12/2 and 20/1 mm Hg higher, respectively, than the corresponding mean daytime ABPM 18.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Mean AOBP was 129/79 mm Hg compared with a mean daytime ABPM of 128/79 mm Hg, whereas oscillometric result was 134/84 mm Hg and the auscultatory result was 132/83 mm Hg, suggesting that AOBP is a more accurate technique than conventional office measurements in the evaluation of an individual's true BP status. Our findings concur with previous results showing similar values for mean AOBP and daytime ABPM, with both values being significantly lower than conventional office readings; this also suggests that white coat hypertension was significantly more prevalent when routine OBP readings were analyzed 6, 8, 16, 17. Staessen et al reviewed 30 studies in which conventional office readings were compared with daytime ABPM in untreated patients with borderline or definite hypertension; their findings showed that mean OBP was 12/2 and 20/1 mm Hg higher, respectively, than the corresponding mean daytime ABPM 18.…”
Section: Discussionsupporting
confidence: 92%
“…that white coat hypertension was significantly more prevalent when routine OBP readings were analyzed. 6,8,16,17 Staessen et al reviewed 30 studies in which conventional office readings were compared with daytime ABPM in untreated patients with borderline or definite hypertension; their findings showed that mean OBP was 12/2 and 20/1 mm Hg higher, respectively, than the corresponding mean daytime ABPM. 18 The main issues of office measurements regarding the white coat effect, observer error, and bias problems are presented mainly by auscultatory devices; therefore, oscillometric devices are almost exclusively used for OBP measurement.…”
Section: |mentioning
confidence: 99%
“…Resting office BP readings, unattended or partially attended, as obtained by automated or semi‐automated oscillometric devices, respectively, significantly underestimate overall daytime systolic BP load as assessed from 24‐h ABPM. Our results are in agreement with report by some, but not all groups 24–30 . There is clinical heterogeneity between studies comparing these two methods including the time gap between the two tests of up to 1 month, time between actual BP readings during AOBP (1 vs. 2 min), number of AOBP readings (ranging from 3 to 5), populations studied (treated vs. untreated; men vs. women; age, etc.)…”
Section: Discussionsupporting
confidence: 92%
“…A recent study concluded that despite their methodological differences, there seems to be considerable similarity between morning home BP and morning ambulatory BP and thus these methods appear to be interchangeable in the assessment of hypertension. [12]…”
Section: Discussionmentioning
confidence: 99%
“…The degree of overestimation by HBPM was lower than OBPM in our study has also shown by Agena et al [6] The manual sphygmomanometer readings could be replaced by automated OBPM reducing errors and are similar to mean awake ABPM. [12]…”
Section: Discussionmentioning
confidence: 99%